Организационная культура как инструмент решения социальных проблем военной сферы - Солнышкина, А. (Социология: теория, методы, маркетинг, 2006)
The author analyses cultural and symbolical codes of the military organizational culture as well as factors determining social problems and pathologies, which obstruct functioning of the military organization in the Ukrainian transformational society.